1985
DOI: 10.1111/j.1365-2125.1985.tb02677.x
|View full text |Cite
|
Sign up to set email alerts
|

Aztreonam in human serum and breast milk.

Abstract: Serum and milk concentrations of aztreonam were studied in 12 lactating, healthy subjects over the 8 h period after the administration of a single intramuscular or intravenous 1 g dose. Milk concentrations of aztreonam were found to be much lower than serum concentrations at all time points after both routes of injection. Peak milk concentrations of aztreonam averaged less than 1% of peak serum concentrations. Times to peak concentrations averaged 6 and 10 times longer in milk than in serum after intramuscular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 5 publications
(4 reference statements)
1
6
0
1
Order By: Relevance
“…This is in agreement with poor lipid solubility, as was mentioned earlier with respect to the CSF. The same applies for the very low concentrations reported in the milk of lactating women (Fleiss et al 1985 …”
Section: Other Compartmentssupporting
confidence: 57%
“…This is in agreement with poor lipid solubility, as was mentioned earlier with respect to the CSF. The same applies for the very low concentrations reported in the milk of lactating women (Fleiss et al 1985 …”
Section: Other Compartmentssupporting
confidence: 57%
“…aztreonam, captopril, diltiazem and (Fehrenbach, 1987). tinidazole (Devlin & Fleiss, 1981;Evaldson et Maternal antimicrobials are often required in Fleiss et al, 1985;Okada et al, 1985). the postnatal period and a prescribing survey in These studies have concentrated on drug kinetics Northern Ireland showed that 4% of puerperal and while this is a very important aspect, previous mothers received metronidazole therapy (Passstudies have given little information about infant more et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…When equal doses of aztreonam were administered by two separate routes, intramuscular and intravenous, to two groups of women the resultant M/P ratios were indistinguishable [7], The ratios obtained after oral or intra muscular administration of butorphanol [8] were clearly different, but this was confounded by the increase in dose for the oral route.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio appears to fall after administration of procainamide [23] and to rise after dosing with baclofen [24], cimetidine [21], hydro chlorothiazide [25] and aztreonam [7], The temporal variance of the M/P ratio for aztreonam was found for two parenteral routes of administration. The pattern of variance can be biphasic, increasing with time then declin ing after 12-16 h for captopril [26], digoxin [27] and phenytoin [11], Pat terns of variation in the M/P ratio for other drugs have been summarized recently [1].…”
Section: Discussionmentioning
confidence: 99%